2016
DOI: 10.1016/j.ijleo.2016.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrothermal growth time on ZnO nanorod arrays photoelectrode performance

Abstract: High density and vertically aligned zinc oxide nanorod arrays (ZnO NRs) have been prepared directly on indium-doped tin oxide (ITO) substrates via two-steps preparation: sol-gel spin coating and hydrothermal process. The nanostructured ZnO was characterized for its morphology, crystalline structure and optical properties by using field emission scanning electron microscopy (FESEM), X-ray diffractometry, and ultraviolet-visible spectroscopy respectively. In addition, the photoeletrochemical (PEC) properties wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 38 publications
3
14
0
Order By: Relevance
“…Conversely, when air bubbles were involved in the growth solution, the ZnO NRs’ (002) diffraction peak in all XRD patterns was dominant with growth time from 0.5 to 5 h as displayed in Figure 8 b. The narrow, sharp, and strong ZnO (002) peaks in the XRD patterns recognized that the ZnO NRs were synthesized along the c-axis with wurtzite hexagonal structure [ 36 , 37 ]. From all the analysis results of ZnO NRs, it can be observed that the air bubbles and growth times played a vital role in the growth of the ZnO structure.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, when air bubbles were involved in the growth solution, the ZnO NRs’ (002) diffraction peak in all XRD patterns was dominant with growth time from 0.5 to 5 h as displayed in Figure 8 b. The narrow, sharp, and strong ZnO (002) peaks in the XRD patterns recognized that the ZnO NRs were synthesized along the c-axis with wurtzite hexagonal structure [ 36 , 37 ]. From all the analysis results of ZnO NRs, it can be observed that the air bubbles and growth times played a vital role in the growth of the ZnO structure.…”
Section: Resultsmentioning
confidence: 99%
“…The coating and pre-heating procedure was conducted thrice. Finally, the coated substrates were annealed for 1 h at 400 °C with 2 °C/min rate [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Highly-oriented perpendicular ZnO nanorods were synthesised at 110°C for four hours on an indium tin oxide (ITO) substrate by hydrothermal technique as demonstrated in earlier reports [21,22].…”
Section: Synthetisation Of Zno Nanorods Arrays (Nras)mentioning
confidence: 99%